PROBLEMS AND PROSPECTS IN COGNITIVE EDUCATION'S GROUNDWORK - Galety, Mohammad Gouse; Josephine, Emilda; Sayfullayev, Anvar; Mamatov, Islom (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2023)
Abstract Studies of the brain and mind, especially those conducted in the last decade, have led to significant advances in our understanding of such critical concepts as learning, memory, intellect, and emotion, all of which have far-reaching consequences for the classroom. A new multidisciplinary subject termed cognitive education has emerged due to these efforts. Still, its potential and limitations have not yet been adequately addressed for it to be officially established as a field of study. This research was conducted to improve current clarity and expand comprehension of cognitive education by zeroing in on its foundational elements.